Global Practices and Trends in the Field of Socially Responsible Business - M. V. Shatokhin; T. G. Antropova; N. M. Suray; O. I. Alaukhova (Вестник Российского экономического университета имени Г. В. Плеханова)
Responsible business – making has gradually entered everybody’s sphere of attention and become the center of interest all over the world in general and academic quarters in particular. The research highlighted this poorly studied subject in the section dealing with the development of ecologic, social and governance (ESG) responsibility in overseas highly-industrialized countries. In these countries pressure on the part of regulation bodies, demands of investors and expectations of society made the greatest contribution to speeding-up the development of ESGpractices. Understanding factors influencing efficiency of ESG-operation of companies was not only the key goal in the sphere of strategic management but possesses fundamental importance for resolving the most urgent ecologic and social problems in the world and for supporting ESG viability. More and more often companies conducting international activities use ESG principles that form the basis for sustainable development of the country. The goal of the article is to provide broad and well-structured knowledge concerning introduction of ESG criteria in overseas countries in order to upgrade national practices in the field of responsible business -making and to identify trends of systemic review of adequate literature sources, comparative analysis and forecasting. The authors compare and analyze the current international status of development in view of rating and describe various steps of governments stimulating movement for ecologic, social and governance responsibility. The article also studied in detail the systems of ESG ratings that are used by key suppliers, as the demand for ESG information keeps growing. Apart from that it provided critical analysis of problems connected with ESG ratings. The growing attention of world community to sustainable development caused a rise in the number ESG rating suppliers, but this extension resulted in additional problems. ESG ratings are complicated and differ depending on the agency due to various methods of assessing and non-standardized information revealing, which can hinder the accurate estimation finding. Moreover, investors and companies demonstrate limited confidence in these ratings accuracy. Standard-legal regulation in different countries aim at improvement of information revealing and comparability of ESG ratings, however discrepancy in criteria of rating assessment and methodology is still present. In the current field of global finance and corporate management ecologic, social and governance aspects have become the key factors influencing investment decisions and forming company strategy. The research can help regulating bodies and politicians develop norms of information revealing in countries with various institutional specific features.